2006
DOI: 10.1038/ni1306
|View full text |Cite
|
Sign up to set email alerts
|

Particularities of the vasculature can promote the organ specificity of autoimmune attack

Abstract: How certain autoimmune diseases target specific organs remains obscure. In the 'K/BxN' arthritis model, autoantibodies to a ubiquitous antigen elicit joint-restricted pathology. Here we have used intravital imaging to demonstrate that transfer of arthritogenic antibodies caused macromolecular vasopermeability localized to sites destined to develop arthritis, augmenting its severity. Vasopermeability depended on mast cells, neutrophils and FcgammaRIII but not complement, tumor necrosis factor or interleukin 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
166
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 45 publications
12
166
1
Order By: Relevance
“…This finding of a normal early, predominantly neutrophil, response but a later defective macrophage response in K/BxN serum-transfer arthritis induced in GM-CSF Ϫ/Ϫ mice is similar to what we observed in the methylated bovine serum albumin-induced peritonitis model in these mice (22). It has been suggested that macrophages are most likely important after the initiation of K/BxN serum-transfer arthritis, being a major source of proinflammatory cytokines (45), whereas neutrophils are required in the early stage involving the vascular permeability that precedes disease onset (46).…”
Section: Discussionsupporting
confidence: 83%
“…This finding of a normal early, predominantly neutrophil, response but a later defective macrophage response in K/BxN serum-transfer arthritis induced in GM-CSF Ϫ/Ϫ mice is similar to what we observed in the methylated bovine serum albumin-induced peritonitis model in these mice (22). It has been suggested that macrophages are most likely important after the initiation of K/BxN serum-transfer arthritis, being a major source of proinflammatory cytokines (45), whereas neutrophils are required in the early stage involving the vascular permeability that precedes disease onset (46).…”
Section: Discussionsupporting
confidence: 83%
“…Because surgery in itself causes tissue damage and inflammation, this might adversely affect leukocyte behavior [10] and essentially precludes obtaining a physiological base line level of homing, which is an important control parameter. Recently, several groups have used non-invasive single-photon techniques such as confocal and near IR imaging to study leukocyte homing [17,18,20]. While these studies represent significant technological advances in their own right, 2P imaging has the advantages of decreased phototoxicity [21] and superior imaging depth that should make it possible to follow cells longer and deeper into tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To separate the effects of mast cells on joint destruction and angiogenesis from the effects of T cell-produced IL-17, we used GPI antibody-induced arthritis that is entirely independent of B cell and T cell activation, because it can be induced even in Rag-2 Ϫ/Ϫ mice (3,11,12). Importantly, injection of GPI antibodies induces arthritis more rapidly than T cells differentiate into distinct functional phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, some diseases such as GPI antibody-induced arthritis are entirely independent of T cells and B cells and thus are especially suitable for selective analysis of mast cell function in vivo (3,11,12). Thus, injection of K/BxN mouse serum containing anti-GPI antibodies into wild-type Kit ϩ /Kit ϩ mice led to severe arthritis within 6 days, characterized by severe edema and functional impairment of the paws 1808 KNEILLING ET AL ( Figure 1A Figures 1C and D), with a mean Ϯ SEM increase in ankle thickness of 480 Ϯ 264 m, 6 days after K/BxN mouse serum transfer.…”
Section: Requirement Of Intraarticular Mast Cells For Development Of mentioning
confidence: 99%
See 1 more Smart Citation